Melejitkan Omset SATT Gresik Melalui Penguatan Literasi Strategi dan Kompetensi Pemasaran Tenaga Marketing: Boosting SATT Gresik's Turnover Through Strengthening Marketing Strategy Literacy and Competence of Marketing Staff - Desembrianita, Eva; Risallah, Fiqi; Mahjudin, Mahjudin (JURNAL PENGABDIAN MANAJEMEN, 2026)
This community service activity aims to improve the marketing performance of PT SATT Gresik by enhancing marketing literacy for the marketing team, which consists of permanent employees and partners of the Muhammadiyah Amal Usaha movement. The training focused on understanding product marketing strategies and developing team competencies amidst the intense competition in the Umrah and Hajj business in Gresik Regency. This activity was conducted by lecturers and students from Muhammadiyah University Gresik as a form of field experience for students. Evaluation was conducted using questionnaires before and after the training. The results showed that participants agreed on the importance of consumer behavior literacy and business environment analysis in supporting marketing. Furthermore, most participants strongly agreed that sustainable marketing literacy and digital marketing strategies are crucial for improving the competency of marketers, which ultimately has a significant impact on increasing sales and attracting pilgrims.